Tamed Hell or Topology of Evil in Early Fiction by Miodrag Bulatović - Lazić, Nebojša J. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
This paper on the early fiction written by Miodrag Bulatović (his so-called homeland fiction) aims to analyse and show that the writer’s insistence on representation of evil among people, in almost all of its forms, is not a goal in its own right, as is the case in the fiction of Marquis de Sade, for example. It is not Bulatović’s intention to tip the balance in favour of the principle of good against the principle of evil. Instead, paradoxically, the reader is lead to a cathartic experience and the triumph of good by way of Rimbaud’s “disorganization of all the senses” experienced by his characters. Bulatović’s fiction is universal because his worldview—recognition of evil in an enormous number of its manifestations—extends beyond the cultural, geographic, and language boundaries. Evil, demonic qualities in people, hatred, hell on earth, life as a long process of dying—all part of the chain of unhappy events in human existence—reach a remarkable degree of cogency on the pages of Bulatović’s fiction, the highest degree that literature is capable of attaining when compared to life.